Cloning, site-directed mutagenesis and expression of single chain fragment variable (SCFV) of C3A8 Hybridoma against breast MCF-7 carcinoma cells in Pichia Pastoris - Syaidatul Najiah Zakaria
The single chain fragment variable (scFv) antibodies of C3A8 hybridoma clone secreted lgM monoclonal antibody against breast cancer cells was constructed earlier by using phage display technology. The recombinant plasmid containing gene of anti-MCF-7 single chain fragment variable antibody was isolated from clone TG1, Escherichia coli and the presence of the gene was confirmed through PCR amplification, restriction digestion and sequencing analysis. The gene was 100% similar to the anti-MCF-7 scFv gene in the GeneBank database (EU980594). In this study, the anti-MCF-7 scFv antibodies gene was cloned and expressed in the Pichia pastoris expresion system as an alternative expression system to the E. coli. The gene was cloned into the pPICZaa expression vector and the new restriction sites, EcoRI_anti-MCF-7 scFv_Not I construct were introduced. The pPICZaa_Ecori_anti-MCF-7 scFv_Not I construct was transformed into P. pastoris strain X-33 and two positive clones were selected (clone 2A1 and 2A6). However, the scFv proteins of these two clones were failed to appear when analysed using SDS-PAGE. The failure was due to the presence of the stop codon at the position nine in the framework region (FR). The gene was re-engineered to a functional anti-MCF-7 scFv gene through site-directed mutagenesis (SDM) by changing the stop codon to serine (S) and modifies the restriction sites from Ecori, Not I to Cla I, Xba I. The mutated Cla I_anti-MCF-7 scFv_Xba I construct was cloned in pPICZaC expression vector and transformed into P. pastoris strain X-33. A 34 kDa anti-MCF-7 scFv antibody band was successfully expressed and observed on the SDS-PAGE gel. The expressed anti-MCF-7 scFv antibodies were characterized by immunoblotting where the band was detected using His-tag peptide which was fused at the carboxyl terminus of the scFv. In conclusion, the functional scFv antibodies were successfully cloned and expressed in P. pastoris through site-directed mutagenesis.